APPLICATION OF TEACHING ENGLISH USING VIDEO-LOG AT RURAL AREA : A CASE OF THAILAND EFL STUDENTS - Novita Dyah Pitaloka; Noviatul Rochmah (PROJECT (Professional Journal of English Education), 2022)
This study reports a case study of english language students and rural area teachers. The purpose of this study is to explore the development of strategies and concepts of language learning on the use of technology media in language learning in rural areas, as well as to determine the extent to which these strategies are feasible to be applied in the learning process despite the inherent mother tongue in communication habits, shortage of english teachers, media learning and limited understanding of basic english. This research has used a qualitative research method with a case study approach. Interview data, observation, and questionnaire narration from language students in this rural area have revealed that their success is mainly based on the V-log, which has increased understanding, motivation, and confidence in learning the language for rural area students. The findings reveal that native students and teachers feel how V-Log helps them understand learning english in emergency remote teaching, students' motivation and confidence to practice and understand english, planning strategies and concepts of learning more efficiently in the future by using technology. In other words, students and teachers have positive perceptions about the use of V-logs in learning english. Keywords:  Rural Area, Strategies And Concepts Learning; Students And Teachers Perspective, Video-Log (V-Log)